Democratic transition in the Muslim world: a global perspective - Stepan, Alfred C. (Religion, culture, and public life, 2018)
Why different democratization outcomes in Tunisia and Egypt? Islamic-Secular Party accommodations, constitutions, militaries, and the content of international assistance -- "Ennadha's democratic commitments, and capabilities : major evolutionary moments and choice" / Rachid Ghannouchi -- "The challenges of democratization in the Arab world : some reflections on the Egyptian case" / Carrie Rosefsky Wickham -- "Mutual accommodation between moderate Islamic and moderate secular activists" / Alfred Stepan -- "The roots of Egypt's constitutional catastrophe : the necessity of marrying analysis of context, process and text" / Nathan J. Brown -- "Civil and political society compromises in the crafting of a progressive and consensual constitution" / Monica Marks -- "Legacies for democratization of prior patterns of civil-military relations" / Hicham bou Nassif -- "Why so much international assistance for an authoritarian military in Egypt and so little for democratic transition and consolidation in Tunisia? / Radwan Masmoudi -- Rethinking other democracies with large muslim populations: what policies helped in Indonesia and india? -- "Crafting Indonesian democracy : inclusion- moderation and the sacralizing of the postcolonial state" / Jeremy Menchik -- "Crafting of a democracy with the world's largest Muslim minority" / Sudipta Kaviraj